2019
DOI: 10.1038/s41598-019-44733-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in H3K4me patterns due to aberrant expression of methyltransferases and demethylases in renal cell carcinoma: prognostic and therapeutic implications

Abstract: Renal cell carcinoma (RCC) is the leading cause among cancer-related deaths due to urological cancers, which results in response to combination of genetic and epigenetic factors. Histone methylations have been implicated in renal tumorigenesis but their clinical significance and underlying pathology are unexplored. Here, we elucidated the histone 3 lysine 4 (H3K4) methylation patterns in clear cell RCC and its underlying pathology. Lower cellular levels of H3K4 mono-methylation, -dimethylation and –tri-methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The present H3K4me3 expression analysis elucidated that high expression levels are correlated with better clinical outcomes being in agreement with previous observation of the prognostic significance of H3K4me3 in renal cell carcinoma [10]. Kumar et al reported that H3K4me3 level was significantly decreased in metastasis of renal cell carcinoma and therefore suggested the implication as a biomarker to discriminate metastatic from nonmetastatic tumors [11]. In contrast, other reports suggested that increased H3K4me3 expression was associated with impaired overall survival in various cancers, such as hepatocellular carcinoma [38], cervical cancer [39], and early-stage colon cancer [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present H3K4me3 expression analysis elucidated that high expression levels are correlated with better clinical outcomes being in agreement with previous observation of the prognostic significance of H3K4me3 in renal cell carcinoma [10]. Kumar et al reported that H3K4me3 level was significantly decreased in metastasis of renal cell carcinoma and therefore suggested the implication as a biomarker to discriminate metastatic from nonmetastatic tumors [11]. In contrast, other reports suggested that increased H3K4me3 expression was associated with impaired overall survival in various cancers, such as hepatocellular carcinoma [38], cervical cancer [39], and early-stage colon cancer [8].…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, immunocytochemistry (ICC) is also applied to confirm histone H3 modification expression in normal and cancer cells [5,7]. Former studies have reported that alteration in the histone modification patterns can provide prognostic information for several cancers, including those detected in colon [8,9], kidney [10,11], lung [5,12], stomach [13], pancreas [14,15], ovary [14], and breast [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) is a leading cause of death among urological cancers. KDM5A facilitates cell proliferation and metastasis via reducing methylated H3K4 [ 107 ]. Silencing KDM5A leads to the induction of apoptosis and cell cycle arrest [ 107 ].…”
Section: Kdm5a In Human Cancermentioning
confidence: 99%
“…KDM5A facilitates cell proliferation and metastasis via reducing methylated H3K4 [ 107 ]. Silencing KDM5A leads to the induction of apoptosis and cell cycle arrest [ 107 ]. KDM5A is also a prognostic indicator for RCC, and it promotes EMT to induce stemness in tumor cells [ 47 ].…”
Section: Kdm5a In Human Cancermentioning
confidence: 99%
“…This overexpression it has been proposed to lead to upregulation of expression of the oncogene c-myc, for example in hepatocellular carcinomas [49]. It will be informative to investigate whether these cells show altered sensitivity to hydroxamates and whether other components of this pathway such as reduced levels of H3K4me3 seen in some cancers, could also provide biomarkers for resistance [50,51].…”
Section: Overexpression Of Sgf29 Also Leads To Tsa Resistance During mentioning
confidence: 99%